The Incidence and Characteristics of Marinacci Anastomosis: An Anatomical Study - Hodzic, Renata; Hodzic, Mirsad; Iljazovic, Ermina; Piric, Nermina; Zukic, Sanela (International Journal of Innovative Research in Medical Science, 2020)
Marinacci anastomosis, also known as Ulnar-Median anastomosis, is an anastomosis in which the branch anastomotic originates proximally in the ulnar nerve and unites distally with the median nerve. A purpose of this study was to determine the incidence and the characteristics of Marinacci anastomosis in the Bosnian population. The 60 anterior forearms of fresh frozen adult cadavers were dissected in the Department of Pathology, University Clinical Centre Tuzla and the morgue of Tuzla during a time period of two years. The Marinacci anastomosis was evidenced in one male forearm in the right side behind the ulnar artery, following an transversal course of 5.2 cm until its connection with the median nerve in only one branch. The incidence of Marinacci anastomosis was 1.67%. Since this anastomosis can expalin some cases where injuries in the forearm nerves are not reflected in the hand muscles, it is important to study. Our study contributes to a limited research on the Marinacci anastomosis, a condition that is rarely found and reported in anatomical research.